The application of oyster reefs in shoreline protection: Are we over‐engineering for an ecosystem engineer?. Issue 7 (29th April 2019) - Morris, Rebecca L.; Bilkovic, Donna M.; Boswell, Maura K.; Bushek, David; Cebrian, Just; Goff, Joshua; Kibler, Kelly M.; La Peyre, Megan K.; McClenachan, Giovanna; Moody, Josh; Sacks, Paul; Shinn, Jenny P.; et al.
Abstract: Oyster reef living shorelines have been proposed as an effective alternative to traditional coastal defence structures (e.g. bulkheads, breakwaters), with the benefit that they may keep pace with sea‐level rise and provide co‐benefits, such as habitat provision. However, there remains uncertainty about the effectiveness of shoreline protection provided by oyster reefs, which limits their broader application. We draw evidence from studies along the east and gulf coasts of the United States, where much research and implementation of oyster reef restoration has occurred, to better define the existing gaps in our understanding of the use of restored oyster reefs for shoreline protection. We find potential disconnects between ecological and engineering functions of reefs. In response, we outline how engineering and ecological principles are used in the design of oyster reef living shorelines and highlight knowledge gaps where an integration of these disciplines will lead to their more effective application. Synthesis and applications . This work highlights the necessary steps to advance the application of oyster reef living shorelines. Importantly, future research should focus on appropriate designs and conditions needed for these structures to effectively protect our coasts from erosion, while supporting a sustainable oyster population, thereby providing actionable nature‐based alternatives for coastal defence to diverse end‐users. Abstract : This work highlights the necessary steps to advance the application of oyster reef living shorelines. Importantly, future research should focus on appropriate designs and conditions needed for these structures to effectively protect our coasts from erosion, while supporting a sustainable oyster population, thereby providing actionable nature‐based alternatives for coastal defence to diverse end‐users.